2001
DOI: 10.2466/pms.2001.93.3.661
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Exertion Scales Attest to Both Intensity and Exercise Duration

Abstract: The present purpose was to study the relationships between perceived exertion (RPE, ETL) and exercise duration for all-out runs eliciting vVO2 max. 12 endurance-trained men performed three exhausting exercises on an indoor track. The first test was an incremental exercise to measure their maximal oxygen uptake (VO2 max), the velocity associated with VO2 max (vVO2 max), the velocity of the lacate concentration threshold (vLT) and the velocity delta 50 (vdelta50: the velocity halfway between vVO2 max and vLT). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 31 publications
2
37
0
1
Order By: Relevance
“…This Values are means ± SD for seven subjects. *Significantly different from H65, P \ 0.05 has previously been shown during cycling exercise (Garcin et al 1998;Garcin and Billat 2001;Nethery 2002) including time trials of maximum effort (Joseph et al 2008), during walking and running exercise (Horstman et al 1979), during exercise in the heat (Nybo and Nielsen 2001a) and during exercise with altered muscle glycogen concentrations (Baldwin et al 2003;Noakes 2004). According to the original concept of Borg (1982), this linear increase in RPE would indicate that the brain perceives that the exercise is becoming progressively more demanding, even though the work rate remains constant.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This Values are means ± SD for seven subjects. *Significantly different from H65, P \ 0.05 has previously been shown during cycling exercise (Garcin et al 1998;Garcin and Billat 2001;Nethery 2002) including time trials of maximum effort (Joseph et al 2008), during walking and running exercise (Horstman et al 1979), during exercise in the heat (Nybo and Nielsen 2001a) and during exercise with altered muscle glycogen concentrations (Baldwin et al 2003;Noakes 2004). According to the original concept of Borg (1982), this linear increase in RPE would indicate that the brain perceives that the exercise is becoming progressively more demanding, even though the work rate remains constant.…”
Section: Discussionmentioning
confidence: 77%
“…In this case, the RPE will rise linearly (Nethery 2002) to reach maximum levels at exercise completion, whether at volitional fatigue (Eston et al 2005(Eston et al , 2006(Eston et al , 2007(Eston et al , 2008Garcin et al 1998Garcin et al , 1999Garcin and Billat 2001;Garcin et al 2003;Horstman et al 1979;Morgan and Borg 1976;Noakes 2004), or at the finish of self-paced time-trial performances (Albertus et al 2005;Garcin et al 2003;Joseph et al 2008;Tucker et al 2004). As a result changes in perception of exertion measured early during exercise may be a sensitive predictor of exhaustion time (Eston et al 2005(Eston et al , 2006(Eston et al , 2007(Eston et al , 2008Garcin and Billat 2001;Horstman et al 1979;Morgan and Borg 1976).…”
Section: Introductionmentioning
confidence: 99%
“…While not fully understood, it is reasonable to assume that ''RPE drift'' results due to a coupling of time-dependent physiological changes (potentially associated with cardiovascular drift) and exertional symptoms detected through sensory pathways and reflected with considerable precision in subjective estimations. Recently Garcin and Billat (2001) showed that RPE responses attest to intensity as well as duration of exercise. Their design utilized high relative (to VO 2 max) running velocities resulting in extremely brief ($5-9 min) bouts.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous research designs have principally examined shorter duration steady workload bouts, this study investigated the correspondence of perceptual estimations of exertion with blood lactate and HR during 60-min cycling sessions. Considering lactate kinetics (Stallknecht et al 1998) and RPE responses (Garcin and Billat 2001), it was hypothesized that a dissociation between perceptual measures and blood lactate would occur.…”
Section: Introductionmentioning
confidence: 99%
“…These scales are complementary tools because the RPE scale is concerned with the current status of the subject (how hard he/she feels the exercise currently is) whereas the ETL scale deals with a subjective prediction of how long the current exercise intensity can be maintained. The concurrent validity of the ETL scale has been studied through the HR (Garcin et al 1999) and exercise relative intensity in various populations (Garcin et al 1999(Garcin et al , 2003(Garcin et al , 2004Garcin and Billat 2001). Moreover, the reliability of the ETL scale has been established during incremental and constant velocity runs in physical education students (Garcin et al 2003) and during field tests in trained male runners (Coquart and Garcin 2007).…”
Section: Introductionmentioning
confidence: 99%